• 2022-06-07
    谓词公式∀xP(x)→∀xQ(x)∨∃yR(y)的前束范式为
    A: ∀x∀z∃y(P(x)→Q(z) ∨ R( y))
    B: ∃x∀z∃y(P(x)→Q(z) ∨ R( y))
    C: ∀x∃y(P(x)→Q(x) ∨ R( y))
    D: ∃x∀y(P(x)→Q(x) ∨ R( y))
  • B

    内容

    • 0

      表达式∀x(P(x,y)∨Q())∧∃y(R(x,y)→∀Zq())中∀x的辖域是() A: P(x,y) B: P(x,y)∨Q(z) C: R(x,y) D: P(x,y)∧R(x,y)

    • 1

      谓词公式(∀x(P(x)∨∃yR(y)))→Q(x)∧R(x)中量词∀x的辖域是 . A: P(x)∨∃yR(y) B: P(x) C: (P(x)∨∃yR(y))→Q(x) D: (∀x(P(x)∨∃yR(y)))→Q(x)∧R(x)

    • 2

      对公式∀x∀y(P(x,y)∨Q(x,z))∧∃xP(x,y)使用代入和换名规则后得到的公式为( )。 A: ∀u∀y(P(u,y)∨Q(u,z))∧∃wP(w,s) B: ∀x∀u(P(x,u)∨Q(x,z))∧∃xP(x,y) C: ∀x∀y(P(x,y)∨Q(x,u))∧∃xP(x,s) D: ∀x∀y(P(x,y)∨Q(x,z))∧∃uP(u,z)

    • 3

      谓词公式(x)(P(x)→Q(x,y)(z)R(y,z)) →S(x)中变元x    。6189ddf3bf26aeeaaf3d4b222c5678c7.gifcc54e24c7778432992553c244851cb68.gif32d769f8fd8371da08be7985dd5e3440.gif

    • 4

      谓词公式x(P(x,y)Q(x,z))R() 中自由变元有()。 A: x B: y, C: z D: x,y,z